2021
DOI: 10.2196/29412
|View full text |Cite
|
Sign up to set email alerts
|

Just-in-Time Adaptive Mechanisms of Popular Mobile Apps for Individuals With Depression: Systematic App Search and Literature Review

Abstract: Background The number of smartphone apps that focus on the prevention, diagnosis, and treatment of depression is increasing. A promising approach to increase the effectiveness of the apps while reducing the individual’s burden is the use of just-in-time adaptive intervention (JITAI) mechanisms. JITAIs are designed to improve the effectiveness of the intervention and reduce the burden on the person using the intervention by providing the right type of support at the right time. The right type of sup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 132 publications
2
27
0
Order By: Relevance
“…These reviews generally found DBCIs to be effective in improving diabetes-related outcomes, particularly HbA 1c [ 51 , 52 , 61 - 64 ], which is in line with our findings; nevertheless, they also concur that the current evidence is limited and there is a need for adequately powered, rigorous trials with long-term follow-ups to determine the clinical and economic impact of such interventions [ 52 , 65 ]. In terms of JITAIs, a recent systematic review investigating popular mental health apps for individuals with depression concluded that JITAI mechanisms have not yet been translated into mainstream depression apps [ 66 ], which also aligns with our findings.…”
Section: Discussionsupporting
confidence: 89%
“…These reviews generally found DBCIs to be effective in improving diabetes-related outcomes, particularly HbA 1c [ 51 , 52 , 61 - 64 ], which is in line with our findings; nevertheless, they also concur that the current evidence is limited and there is a need for adequately powered, rigorous trials with long-term follow-ups to determine the clinical and economic impact of such interventions [ 52 , 65 ]. In terms of JITAIs, a recent systematic review investigating popular mental health apps for individuals with depression concluded that JITAI mechanisms have not yet been translated into mainstream depression apps [ 66 ], which also aligns with our findings.…”
Section: Discussionsupporting
confidence: 89%
“…Beyond their predictive ability, the results around the validity of the digital phenotyping biomarkers hold potential for advancing adaptive interventions [ 25 ]. A key component of adaptive interventions is the tailoring variable that is used to customize treatment at each decision time point [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the causal structure of proximal and distal outcomes, which is usually derived from meta-analyses, process research, optimization trials, or randomized controlled trials (Collins, 2018;Collins et al, 2011), an "ideal" MHI uses information about a target person (e.g., age, gender, location, genome, epigenome, microbiome, blood count results, personality trait, physiological data, specific adverse health behavior, or condition) and that target person's context (e.g., time of the day, weather condition, family or friends close-by) in the most unobtrusive way to predict vulnerable and receptive states. Unobtrusive prediction of these states often requires the use of-in a best-case scenario even noninvasive and contactless-sensors and other technologies to minimize any burden related to MHI use (Jakob et al, 2022;Keller et al, 2022;Teepe et al, 2021).…”
Section: The Anatomy Of An "Ideal" Mobile Health Interventionmentioning
confidence: 99%
“…To this end, receptivity to MHIs is an important aspect to consider that bridges the detection of vulnerable states on the one side (Bent et al, 2021b;Bent, Lu, Kim, & Dunn, 2021a;Coravos, Khozin, & Mandl, 2019;Lekkas, Price, & Jacobson, 2022;Sahandi Far, Stolz, Fischer, Eickhoff, & Dukart, 2021;Sieberts et al, 2021;Teepe et al, 2021), and precision support on the other side (Haug et al, 2020;Hekler, Tiro, Hunter, & Nebeker, 2020;Kramer et al, 2020;Mishra et al, 2021;Schembre et al, 2018).…”
mentioning
confidence: 99%